One decade of “English as a medium of instruction” (EMI) in healthcare education - Alhamami, Munassir (Frontiers in Medicine, 2024)
This paper analyzes published healthcare studies about ‘English as a Medium of Instruction’ (EMI), indexed in the Scopus database from 2013 to 2022. The authors used published criteria of systematic reviews and limited the findings to healthcare education using several key terms; this returned 137 articles. The authors then downloaded and carefully read the articles. The majority of articles (102) were deleted because they did not meet the selection criteria discussed in the methods section, thus the final list comprised 35 research studies. Next, the authors analyzed the articles' bibliometric indexes, such as authors, funding information, context, research instruments, years of publication, place of publication, and citations. In addition, the key findings and recommendations of these studies were presented. Most of the studies assessed were conducted in the last five years in Arabic speaking countries by non-language specialists, and the language of instruction was not the main focus of the studies. The studies were most often about attitudes of students, and used quantitative methods such as questionnaires. The results show diverse and conflicted results such as positive impacts and positive attitudes in some cases, negative impacts and attitudes in others, and preferences for either monolingual or bilingual approaches. The findings demonstrate the need for experimental and rigorous mixed methods studies that involve different stakeholders and are conducted by both applied linguists and healthcare education specialists. Future research should move beyond student attitudes and utilize rigorous mixed methods involving researchers from both linguistics and healthcare education to deepen our understanding of EMI's complex impact in diverse contexts.